Implementasi Pembelajaran Al-Qur’an Hadits Berbasis Modul Ajar Merdeka Belajar di MTS Negeri 1 Langkat - Emha Fidiyan Akhadi; Muhammad Ilham; Sri Fadilah; Fitri Ramadani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
The background to this research is that Al-Qur'an Hadith is part of the educational material taught at MTs Negeri 1 Langkat, and the implementation of the Independent Learning concept in learning Al-Qur'an Hadith is relatively new at MTs Negeri 1 Langkat. The aim of this research is: To determine the implementation of Al-Qur'an hadith learning based on independent learning teaching modules at MTs Negeri 1 Langkat. This research uses this research method, qualitative research is used. The results of this research are that Al Qur'an Hadith learning based on the independent learning teaching module at MTs Negeri 1 Langkat is in accordance with the plans prepared by the Al Qur'an Hadith teacher. The learning implementation includes preliminary activities containing warm-up and apperception, core activities containing material delivery, and closing activities containing formative assessment